Polymorphism TaqIA Gen Dopamine D2 Receptor In Men Aged Start From 40 Years Old With Metabolic Syndrome Compared To Non Metabolic Syndrome - Syahputra, Muhammad Budi (Universitas Muhammadiyah Sumatera Utara, 2019)
Introduction : Metabolic syndrome involves heritability , genetic , bad diet and lack of physical activity . One cause of the Metabolic Syndrome is a genetic abnormality in the dopamine D2 receptor gene that causes